2021
DOI: 10.1021/acsnano.1c00525
|View full text |Cite
|
Sign up to set email alerts
|

Budding and Fission of Nanovesicles Induced by Membrane Adsorption of Small Solutes

Abstract: Membrane budding and fission are essential cellular processes that produce new membrane compartments during cell and organelle division, for intracellular vesicle trafficking as well as during endo-and exocytosis. Such morphological transformations have also been observed for giant lipid vesicles with a size of many micrometers. Here, we report budding and fission processes of lipid nanovesicles with a size below 50 nm. We use coarse-grained molecular dynamics simulations, by which we can visualize the morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 56 publications
0
51
0
Order By: Relevance
“…These shape transformations of nanovesicles are, however, accessible to molecular dynamics simulations. [ 16,17,41–45 ] Here, we focus on two recent simulations [ 16,17 ] which revealed that the leaflet tensions and the concentrations of small solutes, which adsorb onto the membranes, represent important control parameters for the nanovesicle morphologies, see Figure 7 and Section 7.3 further below. In particular, these studies identified parameter values for the formation of membrane necks.…”
Section: Remodeling Of Membrane Shapementioning
confidence: 99%
See 4 more Smart Citations
“…These shape transformations of nanovesicles are, however, accessible to molecular dynamics simulations. [ 16,17,41–45 ] Here, we focus on two recent simulations [ 16,17 ] which revealed that the leaflet tensions and the concentrations of small solutes, which adsorb onto the membranes, represent important control parameters for the nanovesicle morphologies, see Figure 7 and Section 7.3 further below. In particular, these studies identified parameter values for the formation of membrane necks.…”
Section: Remodeling Of Membrane Shapementioning
confidence: 99%
“…Closed membrane necks viewed on nano and micron scales: a,b) Two examples for the hourglass‐like shape of closed necks on the nanoscale where we still resolve the molecular bilayer. Both exterior solutions contain small solutes such as simple sugars (orange) [ 17 ] : a large solute concentration for good solvent conditions in (a) and a small concentrations for poor solvent conditions in (b); and c,d) Optical images of giant vesicles. The scale bar is 10 µm in (c) and 5 µm in (d).…”
Section: Local Properties Of Membrane Necksmentioning
confidence: 99%
See 3 more Smart Citations